Surgical debulking of pituitary macroadenomas causing acromegaly improves control by lanreotide. - Karavitaki, N; Turner, H; Adams, C; Cudlip, S; Byrne, J; Fazal-Sanderson, V; Rowlers, S; Trainer, P; Wass, J (2008)
BACKGROUND: Macroadenomas causing acromegaly are cured surgically in only around 50% of patients. Primary medical treatment with somatostatin analogues has been suggested to be a means of treating patients with a potentially poor surgical outcome. Previous retrospective studies have also suggested that surgical debulking of pituitary tumours causing acromegaly improves control by somatostatin analogues. No prospective study using lanreotide has been carried out thus far to assess whether this is the case. OBJECTIVE: We carried out a prospective study to assess whether surgical debulking of pituitary macroadenomas causing acromegaly improved the subsequent control of acromegaly by the somatostatin analogue lanreotide. PATIENTS AND METHODS: We treated 26 consecutive patients [10 males and 16 females--median age 53.5 years (range 22-70)] with macroadenoma causing acromegaly unselected for somatostatin response for 16 weeks with lanreotide, maximizing GH and IGF-I suppression, if necessary, by incremental dosing. Surgical resection was carried out and the patients were re-assessed off medical treatment at 16 weeks following surgery. Those with nadir GH > 2 mU/l in the oral glucose tolerance test (OGTT) and a mean GH in the GH day curve (GHDC) > 5 mU/l were subsequently restarted on lanreotide and the responses were assessed at the same time points as during the preoperative lanreotide treatment. RESULTS: GH values fell on lanreotide treatment and prior to surgery they were considered 'safe' (mean GH in GHDC < 5 mU/l) in eight patients (30.7%). After surgery, they were 'safe' in 18 patients (69.2%). The figures for normal IGF-I were 11 (42.3%) before surgery and 23 (88.5%) after surgery. After surgery, six patients had nadir GH > 2 mU/l in the OGTT and 'unsafe' GH levels (mean GH in GHDC > 5 mU/l); on re-exposure to lanreotide, GH levels fell in all patients and at the end of 16 weeks postsurgery, they were 'safe' in three of them (50%) (P < 0.05). Pituitary tumour volume was also assessed prospectively, preoperatively on lanreotide and showed a mean fall of 33.1%. Eighty-three percent of patients had > 20% shrinkage. CONCLUSIONS: In this first prospective study using lanreotide, surgical debulking of pituitary tumours causing acromegaly improved subsequent postoperative control by the somatostatin analogue lanreotide. Surgery should, therefore, be considered in patients with macroadenoma causing acromegaly, even if there is little prospect of surgical cure. Lanreotide causes significant pituitary tumour shrinkage in the majority of patients.